Global interprofessional STEM education: A U.S.–Mexico dual degree model for advancing global health competence - Valdez, Gabriela; Hakim, Iman; Colin Gascon, Mary Anne (American Journal of STEM Education, 2026)
This study examines an innovative cross-border dual degree program in medicine and public health developed through a partnership between universities in the United States and Mexico. The program integrates STEM education with interprofessional education (IPE) to prepare students for collaborative leadership in global health systems. Through interdisciplinary coursework, international mobility, and experiential learning in diverse public health contexts, students develop competencies in systems thinking, cultural responsiveness, and interprofessional collaboration. The program also strengthens institutional partnerships, promotes knowledge exchange, and expands global health training opportunities for future healthcare professionals. Findings suggest that cross-border dual degree models can serve as effective platforms for integrating STEM and public health education while fostering globally competent physicians capable of addressing complex health inequities.